Analisis Regresi Linier Sederhana dan Berganda Beserta Penerapannya - Muh Alwy Yusuf; Herman Herman; Trisnawati. H; Ardy Abraham; Hardianti Rukmana (Journal on Education, 2024)
This research is included in the type of causal associative research. The stages of this research on simple linear regression analysis and multiple linear regression are as follows: Variable Identification, Data Analysis then data processing using SPSS software. From the results of the simple regression analysis "the effect of online learning media on student learning outcomes at MTs Dhiyaul Haq Kec. Kalukku Kab. Mamuju" it was found that online learning media had a significant effect on student learning outcomes with a significant level of 0.000 <0.05 or the level of the calculated t value of 8.554> t table value 1.989. Meanwhile, in a study using multiple regression analysis "the effect of education and promiscuity on early marriage" found: 1) partially variable (individual) education with a significant level of 0.000 <0.05 and promiscuity with a significant level of 0.000 <0.05, has a significant effect on early marriage. 2) simultaneously (together) the variables of education and promiscuity have a significant effect on early marriage with a significant level of 0.000 <0.05. Based on the coefficient of determination test in simple regression analysis research, it is found that the percentage of the influence of the online learning model on student learning outcomes is 47.5% and the rest of the percentage, namely 52.5%, is the value of other factors that are not examined and discussed in this study which have a high probability of affecting learning outcomes. Based on the results of the coefficient of determination (R2) test in multiple regression analysis research, the Model Summary table shows that the R Square value reaches a value of 0.407, indicating that the effect of the education and promiscuity variables on the early marriage variable reaches a value of 40.7%. while the rest, namely 59.3% is influenced by other variables that are not in this study.